THE 18TH CONGRESS OF THE COMMUNIST PARTY OF CHINA: NCONCLUSIVE RESULTS, URGENT TASKS, SHAKY COMPROMISES - SYROEZHKIN, Konstantin (CENTRAL ASIA AND THE CAUCASUS, 2013)
The struggle at the very top of China’s political establishment reached its peak on the eve of the 18th Communist Party Congress, which largely predetermined the balance of political forces in the upper echelons of the Communist Party and the decisions made during the congress. The compromise regarding the top figures casts a dim light on the party’s political future. While the retreating Hu-Wen Tandem managed to maintain its position, it is too early to declare that the “reformers” have achieved a final victory; in many respects, the 18th Congress proved to be “transitional.” The final balance of power will likely become clear in five years, after the next, 19th CPC Congress, which will probably clarify the direction of the “fifth generation” of the country’s leaders. The next five years can be characterized as a time of compromises. It must be acknowledged that the criticized Hu-Wen Tandem left the country in relatively good shape, having compiled a reasonable “roadmap” with no alternative in sight. It remains to be seen whether the new party and country leaders will succeed in averting social upheavals and fulfilling the tasks set forth by the 18th Congress while adhering to the roadmap.